Sustainable development goals and nationally determined contributions: the poor fit between agent-dependent and agent-independent policy instruments. Issue 3 (2nd September 2018) - Shockley, Kenneth
Abstract : Sustainable Development Goals (SDGs), which serve as the primary feature of the 2030 Agenda for Sustainable Development, and Nationally Determined Contributions (NDCs), which serve as a vital instrumental of the UNFCCC's Paris Agreement, have clear synergies. Both are focused, in part, on responding to challenges presented to human well-being. There are good practical reasons to integrate development efforts with a comprehensive response to climate change. However, at least in their current form, these two policy instruments are ill-suited to this task. Where SDGs are focused on supporting considerations of human flourishing to which policy needs to respond, NDCs, in their current form, are dependent on the determinations of the nations that generate them. I conclude that the best means of integrating these two policy initiatives require moving past the subjective foundations of NDCs.